Pollen grains bind to lung alveolar type II cells (A549) via lung surfactant protein A (SP-A). Issue 2 (April 1993) - Malhotra, Rajneesh; Haurum, John; Thiel, Steffen; Jensenius, J. -C.; Sim, Robert B.
Abstract : Lung surfactant protein A (SP-A) is the most abundant surfactant-associated protein present in the lung. A receptor for SP-A has been shown to be present on A549 alveolar type II cells and on other cell types, including alveolar macrophage. The SP-A receptor on A549 cells has been identified as the collectin receptor, or C1q receptor, which binds several structurally-related ligands. SP-A contains C-type lectin domains, but the role of carbohydrate binding by SP-A in physiological and pathological phenomena is not yet established. In this paper we report the binding of SP-A to pollen from Populus nigra italica (Lombardy Poplar), Poa pratensis (Kentucky blue grass), Secale cerale (cultivated rye) and Ambrosia elatior (short ragweed). Saturable and concentration dependent binding of SP-A to pollen grains was observed. Interaction of SP-A with pollen grains takes place through waterextractable components, in which the major species present, in Lombardy poplar pollen, are 57 kD and 7 kD (glyco)proteins. The binding of SP-A to pollen grains and their aqueous extracts was calcium ion dependent and was inhibited by mannose, and is therefore mediated by the lectin domain. Binding of SP-A to pollen grains was found to mediate adhesion of pollen grains to A549 cells. The results suggest that pollen grains or other carbohydrate-bearing particles (e. g. microorganisms) could potentially interact with different cell types via the collectin receptor (C1q Receptor) in the presence of SP-A.